Madrasah head academic supervision in improving teacher performance at madrasah Tsanawiyah Negeri 1 Tangerang city - Samsudin, Samsudin; Abdul Rahman; Waska Warta (Jurnal Info Sains : Informatika dan Sains, 2024)
This research aims to (1) understand and analyze the academic supervision of Madrasah principals in improving teacher performance at MTsN1 Tangerang City, (2) to determine the obstacles faced in implementing academic supervision of Madrasah principals to improve teacher performance at Madrasah Tsanawiyah Negeri 1 Tangerang City. The research method used was descriptive method with a qualitative approach. The data collection method is through observation, interviews and documentation. The data analysis technique includes four components, namely, data collection, data reduction, data presentation and drawing conclusions. The research results show that the academic supervision of madrasah principals in improving teacher performance at Madrasah Tsanawiyah Negeri 1 Tangerang City includes the development of syllabi, annual programs, semester programs, lesson plans and KKM which are adapted to student characteristics and relevant educational theories. The supervision model used is a clinical supervision model and artistic supervision with a directive, non-directive and collaborative approach, then the techniques used by the madrasa head are per class, scheduled and programmed techniques, as well as individual conversation techniques, group discussions and madrasa meetings. The obstacles faced in implementing academic supervision of madrasah principals at Madrasah Tsanawiyah Negeri 1 Tangerang City include time, facilities, personnel funds, as well as obstacles in the practice of implementing supervision.